(untitled) (World Bulletin of Public Health, 2024)
This study is devoted to analyzing the application of antiretroviral therapy in HIV-infected patients and evaluating its effectiveness when initiated early and used continuously in Andijan. Materials and Methods. A retrospective analysis was conducted based on the registries of regional Centers for the Prevention and Control of AIDS and patients’ medical records. Research Results. Continuous antiretroviral therapy resulted in virological suppression in 73% of patients, a 12.6% reduction in the proportion of patients with pronounced/severe immunodeficiency, and clinical stability in disease progression